Laser peening electrical aluminum alloy surface modification method based on functionalized absorption layer

By using laser shot peening with a functionalized absorption layer, a dense functional composite layer is formed on the surface of aluminum alloy during the strengthening process. This solves the problems of cumbersome modification steps and poor results in existing technologies, and improves corrosion resistance and electrical conductivity.

CN121373793APending Publication Date: 2026-01-23NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511890318.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing methods for modifying aluminum alloy surfaces are cumbersome and have poor modification effects. Furthermore, traditional laser shot peening processes cannot impart additional corrosion resistance and electrical conductivity during the strengthening process.

Method used

The laser shot peening method using a functionalized absorption layer involves mixing an absorption matrix material with alloy powder to form a slurry, coating it onto the surface of an aluminum alloy, and then using a pulsed laser to perform stepwise scanning impact to form a dense functional composite layer, thereby achieving surface strengthening and functional modification.

Benefits of technology

Simultaneously completing the strengthening and functional modification of the aluminum alloy surface to form a tightly bonded functional composite layer, improving corrosion resistance and conductivity, without the need for additional processes, shortening the production cycle and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121373793A_ABST
    Figure CN121373793A_ABST
Patent Text Reader

Abstract

The invention discloses a laser peening electrical aluminum alloy surface modification method based on a functionalized absorption layer, and belongs to the technical field of surface processing. The pure aluminum powder and the modified alloy powder are uniformly dispersed in the absorbing layer of the laser peening, the absorbing layer is used for absorbing high-pressure plasma shock waves generated by laser energy, powder particles are pressed into the surface of the aluminum alloy matrix at a high speed and combined to the surface of the aluminum alloy matrix, and integrated improvement of matrix surface strengthening, corrosion resistance and conductivity is synchronously achieved. The method is high in process integration degree, the functional layer and the base body are tightly combined, no additional subsequent function modification procedure is needed, and the method can be widely applied to the fields such as aerospace, electronic power and rail transit which have requirements for the comprehensive performance of the aluminum alloy surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface processing technology, specifically relating to a method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer. Background Technology

[0002] Aluminum alloys are widely used in many industrial fields due to their advantages such as low density, high specific strength, and good processability. However, the surface of aluminum alloys is prone to oxidation, forming a loose oxide film, which leads to insufficient corrosion resistance. Furthermore, the presence of the natural oxide film limits the surface conductivity, greatly restricting its application in special environments.

[0003] Laser peening is a technique that strengthens metal surfaces by inducing high-pressure shock waves using pulsed lasers, significantly improving the hardness, fatigue strength, and wear resistance of materials. In traditional laser peening processes, the core function of the absorption layer is to absorb laser energy and generate plasma shock waves. Commonly used materials include black paint and graphite, which only have energy absorption capabilities and cannot impart additional functional properties such as corrosion resistance or electrical conductivity to the substrate surface.

[0004] Existing surface functional modification technologies for aluminum alloys, such as electroplating, electroless plating, and physical vapor deposition, can prepare corrosion-resistant or conductive coatings, but they suffer from problems such as complex processes, weak adhesion between the coating and the substrate, and easy peeling. Some technologies require an additional functional coating preparation step after laser peening, leading to extended production cycles, increased costs, and the possibility that secondary processing may affect the strengthening effect of laser peening. Therefore, developing an integrated technology that can simultaneously achieve surface strengthening and functional modification of aluminum alloys during laser peening has significant engineering application value. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer, so as to solve the technical problems of cumbersome steps and poor modification effect of existing surface functional modification methods for aluminum alloys.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is: to provide a method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer, comprising the following steps: S1. Preparation of functionalized absorbent layer slurry: Mix the absorbent matrix material and alloy powder evenly at a mass ratio of 2-8:1, and then add 30-80wt% dispersion medium to form functionalized absorbent layer slurry; S2. Pre-treatment of aluminum alloy substrate: The surface of the aluminum alloy substrate is degreased, derusted and finely ground. After the impurity removal treatment, the surface roughness of the aluminum alloy substrate is 0.5-2.8μm. S3. Apply functionalized absorption layer: The functionalized absorption layer slurry is uniformly coated on the surface of the pretreated aluminum alloy substrate, and after drying, a functionalized absorption layer with a thickness of 50-200μm is formed. S4. Laser shot peening: First, cover the outside of the absorption layer with a constraint layer of 1-5mm thickness. Then, use a pulsed laser to perform step-by-step scanning impact on the absorption layer. The laser energy density is 6-18GW / cm², the pulse width is 8-45ns, the scanning speed is 4-18mm / s, and the scanning interval is 0.1-0.4mm. The laser energy density needs to balance the shock wave intensity and powder penetration effect, avoiding excessive energy that could lead to powder splashing or matrix damage, while insufficient energy would prevent the formation of an effective functional layer. The absorption layer thickness needs to be matched with the powder particle size to ensure that the powder can be fully propelled by the shock wave and penetrate the matrix. Simultaneously, after surface pretreatment, the parameters of the step-by-step laser scanning are used to perform a single scan of the surface, completing the laser shock. This scan uses conventional laser power and scanning speed to form a molten pool of a certain depth on the aluminum alloy surface, achieving initial surface impact. After the workpiece cools, a second scan is performed on the laser-impacted surface with lower laser power and a faster scanning speed. Lower laser power reduces heat input to the aluminum alloy surface, reduces the heat-affected zone, and avoids overheating and deformation; a faster scanning speed improves processing efficiency and, at lower power, interacts with the aluminum alloy surface to finely process the surface after the first impact, improving the surface microstructure and properties. Maintaining a stable single-step scanning speed ensures uniform powder penetration depth in each impact step, further enhancing the continuity and performance stability of the functional layer.

[0007] S5. Post-processing: Remove the constraint layer and residual absorption layer to obtain the modified aluminum alloy workpiece.

[0008] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the absorbent matrix material is at least one of graphite powder, carbon black, black paint, and nano aluminum powder.

[0009] Furthermore, the alloy powder is a mixture of pure aluminum powder and modified alloy powder in a mass ratio of 2-9:1. The pure aluminum powder has a particle size of 3-45 μm and a purity of ≥99.5%; the modified alloy powder has a particle size of 3-45 μm and a purity of ≥99%.

[0010] Furthermore, the modified alloy powder is at least one of silver powder, copper powder, nickel powder, and tin powder.

[0011] Pure aluminum powder provides the functional layer with basic conductivity and compatibility with the substrate, while modified alloy powders are specifically optimized for their functions. Silver and copper powders focus on improving conductivity, while nickel and tin powders focus on enhancing corrosion resistance. The proportions can be flexibly adjusted according to actual application requirements. Combined with step-by-step scanning and area-by-area impact, powders with different functions are uniformly embedded in the substrate surface, giving full play to their synergistic effect and ensuring the consistency of overall conductivity and corrosion resistance.

[0012] Furthermore, the dispersion medium is ethanol, deionized water, or acrylic resin emulsion.

[0013] Furthermore, S1 can also add 0.3-1.5 wt% of dispersant to the powder material.

[0014] Furthermore, the dispersant is triethanolamine and / or polypropylene glycol.

[0015] Furthermore, the drying temperature in S3 is 60-120℃, and the drying time is 10-30 minutes.

[0016] Furthermore, the materials used for the constraint layer are deionized water, quartz glass, or silicone rubber.

[0017] Furthermore, the thickness of the constraint layer is 0.3-2.5 mm.

[0018] Furthermore, the step-by-step scanning in S4 is as follows: the workpiece is scanned sequentially using scanning powers of 4J, 2J and 1J, while maintaining fixed parameters of 1Hz pulse frequency, 3mm spot diameter and 50% spot overlap rate throughout the process.

[0019] The workpiece is scanned in steps according to the logic of "first constructing a basic layer with conventional parameters, and then finely optimizing with gradient power reduction". The first step uses a conventional laser power of 4J to perform a preliminary scan to form a molten pool of a certain depth. After the workpiece cools down, the second step uses a low power of 2J for fine processing. After cooling down again, the third step uses an even lower power of 1J to complete the final optimization. This step-by-step scanning method forms a gradient structure layer, which reduces heat input and the risk of surface deformation and cracking, while effectively improving the conductivity and corrosion resistance of aluminum alloy, taking into account both processing efficiency and energy consumption.

[0020] Furthermore, the thickness of the functional composite layer on the surface of the modified aluminum alloy workpiece is 40-180μm, and the sum of the mass fractions of pure aluminum and modified alloying elements in the functional composite layer is 10-33%.

[0021] The beneficial effects of this invention are as follows: 1. This invention integrates pure aluminum powder and modified alloy powder into the absorption layer of a laser shot peening process. After absorbing laser energy, the absorption layer rapidly vaporizes and ionizes, generating a high-intensity plasma shock wave. This shock wave acts on the surface of the aluminum alloy substrate, causing plastic deformation and forming residual compressive stress, thus achieving surface strengthening. On the other hand, it propels the functional powder in the absorption layer to impact and press into the substrate surface or into the molten substrate at high speed. Through mechanical interlocking, local metallurgical bonding, and element diffusion, a functional composite layer tightly bonded to the substrate is formed, thereby simultaneously imparting corrosion resistance and electrical conductivity to the surface. This simultaneously completes surface corrosion resistance strengthening and functional modification without the need for additional subsequent processes, shortening the production cycle and reducing production costs.

[0022] 2. This invention can optimize conductivity or corrosion resistance by adjusting the type and ratio of powder and the laser process parameters to meet the needs of different application scenarios. Attached Figure Description

[0023] Figure 1 The change in electrical resistance of 1050 aluminum alloy after treatment with different laser energies; Figure 2 The change in electrical resistance of 6063 aluminum alloy after treatment with different laser energies; Figure 3 The change in polarization resistance of 1050 aluminum alloy after treatment with different laser energies; Figure 4 The change in polarization resistance of 6063 aluminum alloy after treatment with different laser energies; Figure 5 The change in electrical resistance of 1050 aluminum alloy after treatment with different laser remelting powers; Figure 6 The resistance change of 6063 aluminum alloy after treatment with different laser remelting powers. Detailed Implementation

[0024] The specific embodiments of the present invention are described below to facilitate understanding of the invention by those skilled in the art. Unless otherwise specified, specific conditions are applied according to conventional conditions or the manufacturer's recommendations. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various modifications are obvious as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims. All inventions utilizing the concept of this invention are protected.

[0025] Example 1 A method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer includes the following steps: S1. Preparation of functionalized absorbent layer slurry: First, pure aluminum powder, silver powder and nickel powder are mixed in a mass ratio of 6:0.5:0.5 to obtain alloy powder; then, the absorbent matrix material (graphite powder and black paint in a mass ratio of 1:1) is mixed with the alloy powder in a mass ratio of 5:1. Then, 50% ethanol and 1% triethanolamine by mass fraction of the mixture are added to form functionalized absorbent layer slurry. S2. Pre-treatment of aluminum alloy substrate: The surface of the aluminum alloy substrate is degreased, derusted and finely ground. After the impurity removal treatment, the surface roughness of the aluminum alloy substrate is 1-2.5μm. S3. Apply functionalized absorption layer: The functionalized absorption layer slurry is uniformly coated on the surface of the pretreated aluminum alloy substrate and dried at 90℃ for 20 min to form a functionalized absorption layer with a thickness of 100μm. S4. Laser shot peening: First, a constraint layer is covered on the outside of the absorption layer. Then, a pulsed laser is used to perform step-by-step scanning impact on the absorption layer. The workpiece is scanned with scanning powers of 4J, 2J, and 1J in sequence. Throughout the process, the fixed parameters are maintained: pulse frequency of 1Hz, spot diameter of 3mm, and spot overlap rate of 50%. The laser energy density is 10GW / cm², pulse width is 30ns, scanning speed is 10mm / s, and scanning interval is 0.3mm. S5. Post-processing: Remove the constraint layer and residual absorption layer to obtain the modified aluminum alloy workpiece; the thickness of the functional composite layer on the surface of the modified aluminum alloy workpiece is 100μm, and the sum of the mass fractions of pure aluminum and modified alloying elements in the functional composite layer is 21%.

[0026] After pure aluminum and modified alloy powder are incorporated into the laser peening absorption layer, the absorption layer absorbs laser energy and rapidly vaporizes and ionizes to generate a high-intensity plasma shock wave. This shock wave not only causes plastic deformation of the aluminum alloy substrate surface and introduces residual compressive stress to achieve surface strengthening, but also propels the functional powder to impact the substrate at high speed. Through mechanical interlocking, local metallurgical bonding and element diffusion, a tightly bonded functional composite layer is formed. On the one hand, the composite layer relies on the conductive phase of pure aluminum and modified alloy powder to construct a continuous conductive path (the lower the resistivity, the better the conductivity). On the other hand, the dense structure and the passivation film of corrosion-resistant elements improve corrosion resistance (good corrosion resistance can maintain the stability of the conductive path).

[0027] Laser shot peening introduces residual compressive stress into the substrate surface, effectively inhibiting stress corrosion cracking. Modified powder undergoes high-speed compaction and plastic deformation under impact, bonding tightly with the substrate to form a dense composite layer with extremely low porosity and few microcracks. This dense structure significantly delays the deterioration of corrosive media (Cl). -These powder elements (such as O2) penetrate into the matrix through channels. They are uniformly distributed within the composite layer through diffusion. In corrosive environments, they participate in the formation of the surface oxide film, generating a denser, more stable, and more protective composite oxide passivation film. This film has a lower defect density and higher self-healing ability, more effectively blocking corrosion reactions. Excellent corrosion resistance ensures the long-term stability of the composite layer and its internal conductive network in harsh environments, without interruption due to pitting, peeling, or oxidation, maintaining the durability of the low-resistance pathway. Pure aluminum / modified aluminum powder forms a conductive network on the surface of electrical aluminum alloys; laser shot peening breaks the original high-resistance oxide film on the surface, and high-pressure densification reduces interfacial contact resistance.

[0028] Example 2 A method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer includes the following steps: S1. Preparation of functionalized absorbent layer slurry: First, pure aluminum powder, silver powder and tin powder are mixed in a mass ratio of 2:0.3:0.7 to obtain alloy powder; then, the absorbent matrix material (graphite powder) and alloy powder are mixed evenly in a mass ratio of 8:1, and then 80% of the mass fraction of acrylic resin emulsion is added to form functionalized absorbent layer slurry. S2. Pre-treatment of aluminum alloy substrate: The surface of the aluminum alloy substrate is degreased, derusted and finely ground. After the impurity removal treatment, the surface roughness of the aluminum alloy substrate is 0.5-2.8μm. S3. Apply functionalized absorption layer: The functionalized absorption layer slurry is uniformly coated on the surface of the pretreated aluminum alloy substrate and dried at 60℃ for 30 min to form a functionalized absorption layer with a thickness of 50μm. S4. Laser shot peening: First, a constraint layer is covered on the outside of the absorption layer. Then, a pulsed laser is used to scan and impact the absorption layer in stages. The workpiece is scanned with scanning powers of 4J, 2J, and 1J in sequence. Throughout the process, the fixed parameters are maintained: pulse frequency of 1Hz, spot diameter of 3mm, and spot overlap rate of 50%. The laser energy density is 6GW / cm², pulse width is 45ns, scanning speed is 4mm / s, and scanning interval is 0.1mm. S5. Post-processing: Remove the constraint layer and residual absorption layer to obtain the modified aluminum alloy workpiece; the thickness of the functional composite layer on the surface of the modified aluminum alloy workpiece is 40μm, and the sum of the mass fractions of pure aluminum and modified alloying elements in the functional composite layer is 10%.

[0029] Example 3 A method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer includes the following steps: S1. Preparation of functionalized absorbent layer slurry: First, pure aluminum powder and copper powder are mixed at a mass ratio of 9:1 to obtain alloy powder; then, the absorbent matrix material (carbon black) and alloy powder are mixed evenly at a mass ratio of 2:1. Then, 30% of deionized water, 1% of triethanolamine and 0.5% of polypropylene glycol are added to the mixture to form functionalized absorbent layer slurry. S2. Pre-treatment of aluminum alloy substrate: The surface of the aluminum alloy substrate is degreased, derusted and finely ground. After the impurity removal treatment, the surface roughness of the aluminum alloy substrate is 0.5-2.8μm. S3. Apply functionalized absorption layer: The functionalized absorption layer slurry is uniformly coated on the surface of the pretreated aluminum alloy substrate and dried at 120℃ for 10 min to form a functionalized absorption layer with a thickness of 200μm. S4. Laser shot peening: First, a constraint layer is covered on the outside of the absorption layer. Then, a pulsed laser is used to perform step-by-step scanning impact on the absorption layer. The workpiece is scanned sequentially with scanning powers of 4J, 2J, and 1J. Throughout the process, the fixed parameters are maintained: pulse frequency of 1Hz, spot diameter of 3mm, and spot overlap rate of 50%. The laser energy density is 18GW / cm², pulse width is 8ns, scanning speed is 18mm / s, and scanning interval is 0.4mm. S5. Post-processing: Remove the constraint layer and residual absorption layer to obtain the modified aluminum alloy workpiece; the thickness of the functional composite layer on the surface of the modified aluminum alloy workpiece is 180μm, and the sum of the mass fractions of pure aluminum and modified alloying elements in the functional composite layer is 33%.

[0030] Experimental Example Experimental setup: The aluminum alloy matrix materials used in the experiment were 1050 aluminum alloy with the following composition (mass fraction, %): Si 0.25, Fe 0.40, Cu 0.05, Mn 0.05, Mg 0.05, Zn 0.07, Ti 0.05, balance Al; and 6063 aluminum alloy with the following composition (mass fraction, %): Mg 0.52, Si 0.48, Fe 0.18, Cu 0.10, Mn 0.09, Cr 0.08, Zn 0.07, Ti 0.06, balance Al. The two material samples were processed using the method in Example 1. According to GB / T351-2019 "Methods for Measuring the Resistivity of Metallic Materials", the resistance of the laser-treated aluminum alloy samples was measured. The results are as follows: Figures 1-4 As shown, Example 1 is 1050 aluminum alloy and Example 2 is 6063 aluminum alloy.

[0031] from Figure 1 and Figure 2As can be seen, after laser peening, the resistance of both 1050 (corresponding to Example 1) and 6063 (corresponding to Example 2) aluminum alloy conductors decreased, indicating enhanced conductivity and reduced losses. This is because laser peening induces plastic deformation on the material surface through the shock wave induced by a high-energy laser, refining the grains and increasing dislocation density. The refined grains and uniformly distributed dislocations may optimize electron scattering paths, reducing electron scattering at grain boundaries and thus lowering resistance. Simultaneously, the residual compressive stress introduced by laser peening may promote the recombination of internal defects, reducing lattice distortion. A more uniform microstructure reduces the probability of electron scattering, thereby lowering resistance and improving conductivity.

[0032] Figure 3 and Figure 4 The figures show the polarization resistance of laser-peened samples of different aluminum alloys. It can be seen that the polarization resistance of both 1050 and 6063 aluminum alloys increases with increasing laser peening energy. However, the polarization resistance of 6063 aluminum alloy at 2J is not significantly different from that of the untreated sample, which is due to the optimization effect of the laser on the surface structure. For 1050 aluminum alloy, increasing laser peening energy can form a gradient nanocrystalline layer on the surface. Grain refinement and high-density dislocations significantly reduce surface active sites, while the accumulation of residual compressive stress inhibits the penetration of corrosive media, thus continuously increasing the polarization resistance. 6063 aluminum alloy, due to the presence of hard Mg2Si precipitates, has a higher dynamic yield strength than 1050 aluminum alloy. The 2J impact energy failed to break through the strength threshold of the bond between the precipitates and the matrix, resulting in limited surface modification effect. At this point, the shock wave only induces shallow plastic deformation of the matrix, but the Mg2Si phase is not fully broken or dissolved, and its potential difference with the aluminum matrix still dominates, resulting in a slight increase in polarization resistance. When the energy increases to 4J, the impact pressure exceeds the fracture strength of the Mg2Si precipitate, the Mg2Si phase is broken, and the polarization resistance increases significantly.

[0033] 1050 and 6063 aluminum alloys were scanned sequentially using scanning powers of 0, 2000, and 4000 W. Throughout the process, fixed parameters were maintained: a scanning speed of 10 mm / s, a pulse frequency of 1 Hz, a spot diameter of 3 mm, and a spot overlap rate of 50%. Laser remelting of the 1050 and 6063 aluminum alloys was performed, and their resistance changes were as follows: Figure 5 and Figure 6 As shown.

[0034] contrast Figure 1 , Figure 2 (Laser shot peening) and Figure 5 , Figure 6(Laser remelting treatment) As can be seen, the resistance of 1050 and 6063 aluminum alloy conductors under laser shot peening treatment shows a continuous and stable decreasing trend, and the overall resistance reduction effect is more balanced; while in laser remelting treatment, the resistance of 1050 aluminum alloy first decreases and then increases, while the resistance of 6063 aluminum alloy tends to level off in the later stage, failing to achieve continuous optimization. This demonstrates the advantages of laser shot peening: it can induce plastic deformation of the material surface through high-energy shock waves, refine grains and increase dislocation density, and at the same time introduce residual compressive stress to promote the reorganization of internal defects, which not only optimizes the electron scattering path and reduces grain boundary scattering, but also improves lattice distortion and makes the microstructure more uniform, thereby stably reducing resistance and enhancing conductivity. Compared with laser remelting, its optimization effect on resistance is more continuous and the improvement in conductivity is more stable.

Claims

1. A method for surface modification of electrical aluminum alloys by laser shot peening based on a functionalized absorption layer, characterized in that, Includes the following steps: S1. Preparation of functionalized absorbent layer slurry: Mix the absorbent matrix material and alloy powder evenly at a mass ratio of 2-8:1, and then add 30-80wt% dispersion medium to form functionalized absorbent layer slurry; S2. Pre-treatment of aluminum alloy substrate: The surface of the aluminum alloy substrate is degreased, derusted and finely ground. After the impurity removal treatment, the surface roughness of the aluminum alloy substrate is 0.5-2.8μm. S3. Apply functionalized absorption layer: The functionalized absorption layer slurry is uniformly coated on the surface of the pretreated aluminum alloy substrate, and after drying, a functionalized absorption layer with a thickness of 50-200μm is formed. S4. Laser shot peening: First, cover the outside of the absorption layer with a constraint layer of 1-5mm thickness. Then, use a pulsed laser to perform step-by-step scanning impact on the absorption layer. The laser energy density is 6-18GW / cm², the pulse width is 8-45ns, the scanning speed is 4-18mm / s, and the scanning interval is 0.1-0.4mm. S5. Post-processing: Remove the constraint layer and residual absorption layer to obtain the modified aluminum alloy workpiece.

2. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The absorbent matrix material is at least one of graphite powder, carbon black, black paint, and nano aluminum powder.

3. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The alloy powder is a mixture of pure aluminum powder and modified alloy powder in a mass ratio of 2-9:

1.

4. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 3, characterized in that, The modified alloy powder is at least one of silver powder, copper powder, nickel powder, and tin powder.

5. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The dispersion medium is ethanol, deionized water, or acrylic resin emulsion.

6. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, S1 may also add 0.3-1.5 wt% of dispersant to the powder material.

7. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 6, characterized in that, The dispersant is triethanolamine and / or polypropylene glycol.

8. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The drying temperature in S3 is 60-120℃, and the drying time is 10-30 minutes.

9. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The constraint layer is made of deionized water, quartz glass, or silicone rubber.

10. The laser shot peening surface modification method for electrical aluminum alloys based on a functionalized absorption layer according to claim 1, characterized in that, The thickness of the functional composite layer on the surface of the modified aluminum alloy workpiece is 40-180 μm, and the sum of the mass fractions of pure aluminum and modified alloying elements in the functional composite layer is 10-33%.